Effects of 2-amino-9H-pyrido[2, 3-b]indole (AαC) metabolic bio-activation on oxidative DNA damage in human hepatoma G2 (HepG2) cells. (24th March 2018) - Liu, Xianjun; Zhang, Tingting; Li, Xiang; Zhao, Ge; Xie, Fuwei
Abstract: 2-Amino-9H-pyrido[2, 3-b]indole (AαC), which is a hazardous compound present in cigarette smoke, has been listed as probable human carcinogens (Group 2B). The carcinogenicity and genotoxicity of AαC were activated by the process of metabolic bio-activation. Whereas, few studies about genotoxicity induced by AαC have been reported. In this study, we took HepG2 cells as the model to investigate the relationship between oxidative DNA damage induced by AαC and metabolic bio-activation of AαC, which is of importance to unveil the mechanism of AαC genotoxicity. Firstly, the HepG2 cells were treated with 10 and 20 μg/mL AαC, respectively. Then different concentrations of protein ranging from 0 to 1 mg/mL in S9 mixture solution were utilized to make cells have different capacities for metabolic activation. Intracellular AαC hydroxylated metabolites and 8-OHdG were estimated by using ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS). The results showed that, at the same concentration of AαC, with the increment of concentration of protein in S9 mixture solution, the levels of hydroxylated metabolites and 8-OHdG/10 6 dG increased. And at the same concentration of protein in S9 mixture solution, with the increment of concentration of AαC, the levels of hydroxylated metabolites and 8-OHdG/10 6 dG increased. The hydroxylated metabolites and 8-OHdG were positively related by correlation analysis. In addition, the correlation coefficients of N-OH-AαC and 8-OHdG were maximum ( R 2 = 0.73 and 0.66). Taken together, these results indicated that the metabolic bio-activation of AαC might result in oxidative DNA damage.